The Normality of a Virtual Laboratory - Elena LACATUS (Communications of International Proceedings, 2021)
The Covid 19 pandemic became the catalyst for the digitization process when research laboratories equipped with state-of-the-art experimental facilities and analytical equipment became unusable for more than a year and a half. Teams of researchers, professors and students continued in the virtual environment the research that had once been carried out in laboratories, creating virtual applications capable of describing experiments carried out physically in normal times. Digitizing experiments and generating experimental databases were the first steps in creating Digital Twins of equipment and facilities in research laboratories. The accumulated experience has shown that post-pandemic laboratories will no longer be like those of the past, while the digitization of experiments and the generation of virtual laboratories will become the new benchmark
Keywords: Digital Twin; Virtual Laboratory; Digital Transformation